Analisis Kebutuhan dan Perancangan Antarmuka Pengguna Situs Web Pet N Pop menggunakan Metode Goal-Directed Design dan Post-Study System Usability Questionnaire (Studi Kasus : PT Mahitala Bramanta Digital) - Nabilah Wava Elazri; Satrio Hadi Wijoyo; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT Mahitala Bramanta Digital has a brand called Pet N Pop, the company wants the Pet N Pop to issue various types of products. These products are Point of Sales specifically for Pet Shops and event services. To make it easier for users to find out the products provided by Pet N Pop, Pet N Pop requires a website interface design that is good and easy to use by users. This research was conducted with the aim of producing a user interface design for the Pet N Pop website using the Goal-Directed Design (GDD) method which consists of 6 phases. The research phase is useful for finding the needs desired by stakeholders and users. The modeling phase produces a user persona that describes the user with the contents of 4 variables and also the prospective user journey. Requirements phase, generate scenario context and arrange what is needed in the design. The framework phase, produces a web site user interface framework in the form of wireframes. Refinement phase, perfecting the user interface framework in the form of a high-fidelity prototype. The support phase carried out qualitative and quantitative testing using usability testing techniques and distributing PSSUQ questionnaires to 9 respondents. The end result of this research get good feedback from users because users feel that this website is easy to understand and can meet their needs. This website gets an average score of 1.78 on the overall scale of the PSSUQ questionnaire which indicates that the usability level of the design designed by the researcher is high and the users are satisfied.